Penegakan Hukum Pertambangan Timah Ilegal Pasca Kasus Korupsi Tata Niaga Timah Di Bangka Belitung - La Antrag, Imanuel; Tesalonika Situmaeng, Yanti; Arinda, Suci; Aulia Rochim, Aditya (CV. Multi Kreasi Media, 2024)
Illegal tin mining in Bangka Belitung remains a critical issue that requires serious attention. Corruption in mining governance has resulted in significant financial losses for the state and exacerbated environmental damage. This research aims to evaluate law enforcement efforts and strategies to strengthen the non-mining economic sector to create more transparent and sustainable governance. The research method used is normative juridical, analyzing existing regulations, case studies, and interviews with relevant stakeholders. The research findings indicate that institutional and regulatory strengthening is necessary, including the establishment of an independent supervisory body authorized to oversee all aspects of tin mining and the imposition of strict sanctions for violations. Additionally, economic diversification through the development of tourism, MSMEs, and agriculture has proven effective in reducing the community's dependency on illegal tin mining. Government support in the form of training, access to capital, and infrastructure is crucial to promote sustainable economic growth and create new job opportunities. Consistent and sustainable law enforcement is also a key factor in tackling illegal mining. Strengthening coordination among law enforcement agencies and using modern technology to enhance monitoring effectiveness are essential. The conclusion of this research emphasizes that a comprehensive and inclusive approach to regulatory strengthening, economic diversification, and law enforcement can create more transparent, accountable, and sustainable tin mining governance, providing maximum benefits for the community and environment in Bangka Belitung.